NUGGET DAN KERUPUK IKAN TONGKOL SEBAGAI ALTERNATIF USAHA UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT - Ningrum dwi Hastuti; Refid Ruhibnur (Fakultas Pertanian Universitas Yudharta Pasuruan, 2016)
Potential outcomes catching tuna by fishermen in the village Suka Bangun Dalam this very nice with abundant results which reached an average of 7tons/day . The research objective knowledge partners want to know about the diversification of processed tuna into nuggets andchips . The methods used are education and training by means of a live demonstration of theprocessed tuna into nuggets and chips . Achievement on the training of making tuna into nuggets and chips are all participants partners to make nuggets and chips well and their packaging. The results showed that 90% of business partners can make products nuggets and chips sword fish well .